Fecal Short-Chain Fatty Acids Levels Were Not Associated With Autism Spectrum Disorders in Chinese Children: A Case–Control Study - Wang, Jue; Pan, Jialiang; Chen, Hengying; Li, Yan; Amakye, William Kwame; Liang, Jingjing; Ma, Bingjie; Chu, Xinwei; Mao, Limei; Zhang, Zheqing (Frontiers in Neuroscience, 2019)
Evidence in animal models support that short chain fatty acids (SCFAs), a subset of key gut microbial metabolites, are linked to autism spectrum disorders (ASD), however findings from human studies on this topic are unclear. We aimed to investigate whether fecal SCFAs are associated with ASD in Chinese children aged 6-9 years old. A total of 45 ASD children aged 6-9 years and 90 sex- and age-matched neurotypical controls were enrolled. High-performance liquid chromatography was applied to quantify 10 SCFA subtypes in feces. Dietary and other socio-demographic information were obtained via face-to-face interview using questionnaires. After adjustment for multiple comparisons, paired t test analysis indicated that the fecal total and subtypes of SCFAs concentrations were comparable in autistic children and the controls. Conditional logistic regression analysis showed that there was no significant relationship between the fecal concentration of SCFAs and the risk of ASD after adjustment for age, sex, BMI, breastfeeding, mode of delivery, parental education level, and daily energy, protein, fat and fiber intake. In conclusion, our results did not support the hypothesis that fecal SCFAs levels might be associated with the presence of ASD. However, SCFA measurement was based on a single test of stool sample, therefore this conclusion should be treated with caution. Further studies with measurement of long-term bodily SCFAs concentrations are needed to examine this relationship.